Expériences d'accouchement en milieu hospitalier au Québec : asymétrie des rapports de pouvoir, injustice épistémique et violences obstétricales - Ferreira, Nathalie (Université du Québec à Montréal, 2023)
Historiquement, la grossesse et l'accouchement étaient le champ de pratique des sages-femmes et traduisaient les savoirs empiriques qu’elles et d’autres femmes avaient développés sur leur corps. Mais, aux 19e et 20e siècles, en Occident, les sages-femmes perdent la main mise sur l'accouchement au profit de la nouvelle profession médicale omnipotente, métier historiquement réservé aux hommes. L’obstétrique-gynécologie voit le jour sous la lunette misogyne et raciste d’hommes qui tentent de mener cette spécialité vers la reconnaissance et la gloire auprès de leurs pairs, parfois aux dépens des femmes surtout noires ou pauvres. De nos jours, au Québec et à travers le monde, des voix s’élèvent pour dénoncer la violence obstétricale subie par les personnes qui accouchent : des abus, des mauvais traitements et des non-respects des droits des personnes vécus durant la grossesse et l’enfantement. Ainsi, c’est avec une posture épistémologique féministe que cette recherche tente, à partir de témoignages de femmes ayant enfanté dans le milieu hospitalier au Québec, de comprendre l’expérience d’accouchement dans un lieu où les rapports de pouvoir sont inégaux. Cette recherche qualitative croise les données avec deux théories clés : les savoirs faisant autorité et l’injustice épistémique. Trois points saillants ressortent de l’analyse : 1) ce sont les soignant·es qui détiennent les savoirs faisant autorité et avec eux le pouvoir décisionnel dans la salle d’accouchement. 2) Les personnes qui accouchent sont victimes d’injustice testimoniale au moment de l’enfantement. 3) L’injustice herméneutique nuit à la reconnaissance et à la lutte contre les violences obstétricales. Finalement, cette recherche met en lumière que les injustices épistémiques que vivent les personnes qui accouchent en milieu hospitalier au Québec sont la toile de fond dans laquelle s’enracinent les violences obstétricales. L’analyse témoigne de la nécessité de renverser les rapports de pouvoir inégaux dans la salle d’accouchement et de changer de paradigme autour de la naissance afin d’obtenir plus de justice périnatale. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Injustice épistémique, savoirs faisant autorités, violence obstétricale, accouchement, justice périnatale, rapports de pouvoir.
https://uqam-bib.on.worldcat.org/oclc/1373308699
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; biblioFem*; discipline; droits des femmes*; injustices épistémiques; inégalités; maternité; mémoires/thèses; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; travail social; violences; étude qualitative

Challenging the “old boys club” in academia: Gender and geographic representation in editorial boards of journals publishing in environmental sciences and public health - Dada, Sara; van Daalen, Kim Robin; Barrios-Ruiz, Alanna; Wu, Kai-Ti; Desjardins, Aidan; Bryce-Alberti, Mayte; Castro-Varela, Alejandra; Khorsand, Parnian; Santamarta Zamorano, Ander; Jung, Laura; Malolos, Grace; Li, Jiaqi; et al. (PLOS Global Public Health, 2022)
In light of global environmental crises and the need for sustainable development, the fields of public health and environmental sciences have become increasingly interrelated. Both fields require interdisciplinary thinking and global solutions, which is largely directed by scientific progress documented in peer-reviewed journals. Journal editors play a critical role in coordinating and shaping what is accepted as scientific knowledge. Previous research has demonstrated a lack of diversity in the gender and geographic representation of editors across scientific disciplines. This study aimed to explore the diversity of journal editorial boards publishing in environmental science and public health. The Clarivate Journal Citation Reports database was used to identify journals classified as Public, Environmental, and Occupational (PEO) Health, Environmental Studies, or Environmental Sciences. Current EB members were identified from each journal’s publicly available website between 1 March and 31 May 2021. Individuals’ names, editorial board roles, institutional affiliations, geographic locations (city, country), and inferred gender were collected. Binomial 95% confidence intervals were calculated for the proportions of interest. Pearson correlations with false discovery rate adjustment were used to assess the correlation between journal-based indicators and editorial board characteristics. Linear regression and logistic regression models were fitted to further assess the relationship between gender presence, low- and middle-income country (LMIC) presence and several journal and editor-based indicators. After identifying 628 unique journals and excluding discontinued or unavailable journals, 615 journal editorial boards were included. In-depth analysis was conducted on 591 journals with complete gender and geographic data for their 27,772 editors. Overall, the majority of editors were men (65.9%), followed by women (32.9%) and non-binary/other gender minorities (0.05%). 75.5% journal editorial boards (n = 446) were composed of a majority of men (>55% men), whilst only 13.2% (n = 78) demonstrated gender parity (between 45–55% women/gender minorities). Journals categorized as PEO Health had the most gender diversity. Furthermore, 84% of editors (n = 23,280) were based in high-income countries and only 2.5% of journals (n = 15) demonstrated economic parity in their editorial boards (between 45–55% editors from LMICs). Geographically, the majority of editors’ institutions were based in the United Nations (UN) Western Europe and Other region (76.9%), with 35.2% of editors (n = 9,761) coming solely from the United States and 8.6% (n = 2,373) solely from the United Kingdom. None of the editors-in-chief and only 27 editors in total were women based in low-income countries. Through the examination of journal editorial boards, this study exposes the glaring lack of diversity in editorial boards in environmental science and public health, explores the power dynamics affecting the creation and dissemination of knowledge, and proposes concrete actions to remedy these structural inequities in order to inform more equitable, just and impactful knowledge creation.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; discipline; discours dominant; intersectionnalité; médecine; projet charge mentale; périodes historiques; racisme; santé; santé publique; sciences; sexisme; systèmes d'oppressions; thématiques

Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Unlocking the Power of Allyship: Giving Health Care Workers the Tools to Take Action Against Inequities and Racism - Noone, Damien; Robinson, Lisa A.; Niles, Chavon; Narang, Indra (NEJM Catalyst Innovations in Care Delivery, 2022)
Everyone, not just marginalized groups, must fight racism and oppression. Members of privileged groups must learn to be allies. Toronto’s Hospital for Sick Children developed a series of workshops to teach them how.Summary Oppression and racism are pervasive in the health care environment and directly impact patients, physicians, and other health care practitioners. Fostering and promoting allyship skills can increase inclusion in health care and advance systemic change. The Hospital for Sick Children in Toronto developed a foundational allyship workshop to increase awareness and understanding of interpersonal, systemic, and institutional oppression and discrimination in the large pediatric academic center. The workshop emphasizes individual accountability and how to speak up and act against oppression through critical allyship. The authors report promising results around the engagement and desire to practice allyship amongst health care providers.
Keywords: allié·e·s; amériques; approches et analyses; canada; cours; discipline; médecine; ontario; oppression; premier cycle; pédagogie; pédiatrie; racisme; régions géographiques; résistance; santé; sciences; sex2283; systèmes d'oppressions; thématiques; toronto; violences

The feminist political economy of Covid-19: Capitalism, women, and work. - Cohen, Jennifer; van der Meulen Rodgers, Yana (Global public health, 2021)
Analysing the pandemic through a feminist political economy lens makes clear how gender, race, and class structures are crucial to the functioning of capitalism and to understanding the impacts of the pandemic. The way capital organises production and reproduction combines with structures of oppression, generating vulnerability among the racialised and gendered populations worst impacted by Covid-19. Using global data, this commentary shows that during the pandemic, women experienced relatively greater employment losses, were more likely to work in essential jobs, and experienced a greater reduction in income. Women were also doing more reproductive labour than men and were more likely to drop out of the labour force because of it. Analyses of capitalism in feminist political economy illustrate how capital accumulation depends on women's oppression in multiple, fundamental ways having to do with their paid and unpaid work. Women's work, and by extension their health, is the foundation upon which both production and social reproduction rely. Recognising the pandemic as endogenous to capitalism heightens the contradiction between a world shaped by the profit motive and the domestic and global requirements of public health.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; capitalisme; covid-19; histoire et politique; patriarcat; projet charge mentale; périodes historiques; racisme; ressource en ligne; santé; sexisme; systèmes d'oppressions; thématiques; violences

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Undocumented mothers and work–family conflict in restrictive policy contexts - Straut-Eppsteiner, Holly (Journal of Marriage and Family, 2021)
Objectif Cette recherche examine la manière dont les mères latines sans papiers négocient le conflit travail-famille dans un contexte de politiques d’immigration restrictives. Arrière-plan Aux États-Unis, les femmes continuent de lutter contre les tensions entre travail et famille, et les femmes pauvres sont confrontées à des contraintes particulières. Les immigrées latinos se sont de plus en plus installées et ont fondé des familles aux États-Unis, et ont rejoint le marché du travail dans des emplois à bas salaires. Contrairement aux femmes nées aux États-Unis, ces femmes doivent faire face à des politiques d’immigration restrictives, ce qui suggère de nouveaux domaines de compréhension des inégalités intersectionnelles qui façonnent le conflit travail-famille. Méthode Les résultats sont basés sur des entretiens approfondis menés auprès de 45 mères immigrantes latinos en Caroline du Nord qui avaient une expérience du marché du travail rémunéré. Les sujets d'entretien comprenaient la famille, le travail et la migration tout au long de la vie des femmes. Résultats Les contextes politiques spécifiques au lieu, les conditions de travail, les attentes patriarcales et le manque d'accès aux réseaux de soins remettent en question la capacité des immigrantes latines à remplir le double rôle de mère qu'elles occupent à la fois en tant que pourvoyeuses de famille et en tant que soignantes et nourricières de leurs enfants. Conclusion Les attentes sociales liées à la maternité ajoutent une dimension de précarité au statut vulnérable des femmes en tant que travailleuses sans papiers et démontrent l’impact genré des politiques d’immigration. Conséquences Les politiques restrictives rendent de plus en plus difficile pour les femmes sans papiers d’obtenir ou de changer d’emploi sur le marché du travail à bas salaires. Les résultats soulignent l’importance de prendre en compte le statut d’immigrant dans les études sur les conflits travail-famille, en particulier à l’heure où les politiques ciblant les immigrés s’intensifient.
Keywords: amériques; approches et analyses; conciliation famille-travail; famille; femmes latino-américaines; femmes migrantes*; inégalités; patriarcat; politiques migratoires; projet charge mentale; racisme; régions géographiques; santé; santé mentale; sexisme; systèmes d'oppressions; thématiques; travail; travail reproductif; états-unis

Kuei, je te salue: conversation sur le racisme - Béchard, Deni Ellis; Kanapé Fontaine, Natasha (Éditions Écosociété, 2020)
« En 2016, la poète lnnu Natasha Kanapé Fontaine et le romancier québéco-américain Deni Ellis Béchard entamaient une conversation sans tabou sur le racisme entre Autochtones et Allochtones. Comment cohabiter si notre histoire commune est empreinte de honte, de blessures et de colère? Comment faire réaliser aux Blancs le privilège invisible de la domination historique? Comment guérir les Autochtones des stigmates du génocide culturel? Ces questions traversent leurs échanges: Natasha raconte sa découverte des pensionnats autochtones, son obsession pour la crise d'Oka, la vie dans la communauté de Pessamit ; Deni parle du racisme ordinaire de son père, de la ségrégation envers les Afro-Américains, de son identité de Québécois aux États-Unis. Cinq ans plus tard, Deni et Natasha reprennent la plume pour poursuivre ce "rendez-vous de la parole qui s'ouvre". Renouant avec le ton intimiste et le foisonnement intellectuel de leur premier échange, ils abordent des sujets d'une brûlante actualité: mobilisation de Black Lives Matter après la mort de George Floyd, feux de forêt en Californie, campagne présidentielle sur fond de montée de l'intolérance; soulèvement des Wet'suwet'en et blocus ferroviaires, dénonciation de la politique de la reconnaissance du gouvernement Trudeau. Puis survient l'impensable: Joyce Echaquan, une Atikamekw de 37 ans, meurt sous les injures racistes de deux infirmières de l'hôpital de Joliette. Une vague d'indignation monte ...»–Quatrième de couverture.
Section: 203 pages ; 22 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires